WHAT ARE THE CRITERIA USED IN UZBEKISTAN TO MEASURE POVERTY? (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article defines poverty from an economic and social perspective, discusses its symptoms, and suggests ways to reduce it in Uzbekistan a problem that plagues many nations' economies. Details were given regarding the four primary approaches used to measure poverty, some of which are unique to the Uzbek economy, and pertinent recommendations were developed.